2012
DOI: 10.3892/ijmm.2012.922
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin prevents the apoptosis of NIT-1 cells induced by TNF-α via the PI3K/Akt and MAPK signaling pathways

Abstract: Abstract. The kallikrein-kinin system (KKS) is a complex multi-enzyme system which is composed of circulating and tissue kallikrein and kinin. It is well established that tissue kallikrein and kinin play crucial and diverse roles in cardiovascular and renal homeostasis. Recent data indicate that kallikrein gene delivery reduces insulin resistance in STZ-treated rats suggesting a protective role for kinin in the development of diabetes. This study investigated the effects of exogenous bradykinin (BK) on the apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…KKS is a complex multi-enzyme system composed of circulating and tissue kallikrein and kinin. It is well established that tissue kallikrein and kinin play crucial and diverse roles in cardiovascular and renal homeostasis [10]. Our previous data also show that kallikrein gene delivery reduces blood pressure and ameliorates renal function in spontaneously hypertensive and 5/6 nephrectomized rats [11].…”
Section: Introductionmentioning
confidence: 52%
“…KKS is a complex multi-enzyme system composed of circulating and tissue kallikrein and kinin. It is well established that tissue kallikrein and kinin play crucial and diverse roles in cardiovascular and renal homeostasis [10]. Our previous data also show that kallikrein gene delivery reduces blood pressure and ameliorates renal function in spontaneously hypertensive and 5/6 nephrectomized rats [11].…”
Section: Introductionmentioning
confidence: 52%
“…PI3K-dependent Akt activation has been shown to play an important role in BK-mediated cellular functions [26,27,39]. We demonstrated that treatment with a PI3K inhibitor and Akt inhibitor inhibited BK-induced cell motility and ICAM-1 expression, suggesting that PI3K/Akt activation is a requisite event in BK-increased cell migration in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 61%
“…PI3K/Akt activation has been reported to occur in BK-mediated cell functions [26,27]. To examine whether PI3K is involved in BK-induced cell migration, the PI3K inhibitor Ly294002 was used.…”
Section: Resultsmentioning
confidence: 99%
“…This seems to corroborate the findings reported so far in animal models 33,34 as well as experimental studies on degenerative disease and cell aging processes in humans. 24,25,[35][36][37][38][39] Our results concerning oxidative stress in C1--INH -HAE as well as the effect of bradykinin on oxidative stress in PBMCs in this patient population were presented as preliminary findings during 2018 Bradykinin Symposium in Berlin. 40 They are generally consistent with the recent study by Del Giacco et al, 18 who indicated Our results concerning the effect of exogenous bradykinin on basal and H 2 O 2 -induced ROS levels in PBMCs in patients with C1 -INH -HAE showed that bradykinin exerted a significant antioxidant effect in this group of patients.…”
Section: What's New?mentioning
confidence: 83%